2002
DOI: 10.1159/000066788
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Polycystic Kidney Disease – Clinical and Genetic Aspects

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is one of the most common inherited disorders in humans. It accounts for 8–10% of the cases of end-stage renal disease worldwide, thus representing a serious medical, economical and social problem. ADPKD is in fact a systemic disorder, characterized with the development of cysts in the ductal organs (mainly the kidneys and the liver), also with gastrointestinal and cardiovascular abnormalities. In the last decade there was significant progress in uncovering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 145 publications
(156 reference statements)
0
8
0
1
Order By: Relevance
“…The above-mentioned histologic and ultrastructural characteristics of renal cysts in the pc mutant closely resemble those of PKD, particularly autosomal-dominant PKD [12,13] and its murine models [3,4]. Furthermore, the medaka polycystic kidney disorder also resembles autosomal-dominant PKD in its slowly progressive nature, which supported a relatively long life of the affected fish.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The above-mentioned histologic and ultrastructural characteristics of renal cysts in the pc mutant closely resemble those of PKD, particularly autosomal-dominant PKD [12,13] and its murine models [3,4]. Furthermore, the medaka polycystic kidney disorder also resembles autosomal-dominant PKD in its slowly progressive nature, which supported a relatively long life of the affected fish.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, we examined the early stages of cystic formation at the microscopic level, showing that cystic formation occurs in the pronephros and then the mesonephros at larval stages before it can be visualized by the naked eye. Based on these results, we concluded that the kidney disorder in the pc mutant is a mesonephric counterpart of PKD, particularly an autosomal-dominant PKD [12,13]. Thus, the pc mutant is a good mesonephric model for the study of PKD.…”
mentioning
confidence: 94%
“…Its progression rate varies greatly between patients and about 50% of subjects with ADPKD eventually reach ESRD [9]. The reason for this individual variability is not yet fully understood and can only be partly explained on the basis of various genetic-environmental patterns.…”
Section: Discussionmentioning
confidence: 99%
“…PKD1 mutations cause ADPKD in the majority of cases, leading to severe impairment of kidney function and accompanying systemic damage. 1,2 Both polycystins interact via their cytosolic C-terminal regions 3,4 and are integral parts of a common signal transduction pathway. 1 Polycystin-1 (TRPP1) is the only 11 transmembrane domainscontaining protein that belongs to the superfamily of transient receptor potential channels (TRPs), normally characterized by six transmembrane spans.…”
Section: Introductionmentioning
confidence: 99%